ÉVALUATION DE L’EFFET INHIBITEUR DES HUILES ESSENTIELLES DE LAVANDULA LATIFOLIA VIS-À-VIS DE CORYNEBACTERIUM AMMONIAGENES ATCC 6872 ET DE SON MUTANT CH31. - Lamine, Benine Mohamed; Ismahame, Azzi; Kelthoum, Larbi Daouadji; Khadouja, Kanoun; Bouziane, Abbouni (European Scientific Journal, ESJ, 2015)
The abusive use of antibiotics in human and veterinary medicine create a selective pressure on bacterial populations, This produces the emergence of multi-resistant bacterial strains leading to treatment failures and an additional cost anti-infective treatments. These findings call for finding other alternative treatments. The aim of this study is the evaluation of the antibacterial properties of the essential oils of the leaves of Lavandula latifolia harvested from Sidi Bel Abbes region (Algeria), which were evaluated against Corynebacterium ammoniagenes ATCC 6872 and its CH31 mutant, by the using agar well diffusion method and by the study of bacterial growth in the absence and the presence of essential oils. The obtained results showed that the antibacterial activity of the essential oils of the leaves of Lavandula latifolia at various concentrations has indicated an excellent antibacterial activity by Corynebacterium ammoniagenes ATCC 6872 and its CH31 mutant, with a average values of I50 = 0.06 mM et I50= 0.1 mM respectively. Furthermore, the study of CH31 mutant growth in the absence (control) and in the presence of the essential oils of the leaves of Lavandula latifolia has manifested a considerable biomass reduction accompanied with unbalanced growth after adding of the crude extract.